2017
DOI: 10.1007/s10792-017-0526-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical features and visual outcomes of pars planitis

Abstract: Pars planitis is an idiopathic chronic intermediate uveitis mostly affecting children and adolescents. In spite of its chronic nature with high potential of causing ocular complications, adequate treatment and close follow-up lead to favorable visual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
6
0
7
Order By: Relevance
“…Intermediate uveitis is characterised by chronic inflammatory cell aggregates on the pars plana (snowbanks) and within the vitreous (snowballs). In spite of its chronicity and the potential for ocular complications, adequate treatment and close follow-up may suffice for favourable visual outcomes 1. Intermediate uveitis in children is rare; one study found the prevalence of non-infectious intermediate uveitis for paediatric patients, 0 (95% CI, 0.1 to 1.1) per 100 000 2…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate uveitis is characterised by chronic inflammatory cell aggregates on the pars plana (snowbanks) and within the vitreous (snowballs). In spite of its chronicity and the potential for ocular complications, adequate treatment and close follow-up may suffice for favourable visual outcomes 1. Intermediate uveitis in children is rare; one study found the prevalence of non-infectious intermediate uveitis for paediatric patients, 0 (95% CI, 0.1 to 1.1) per 100 000 2…”
Section: Discussionmentioning
confidence: 99%
“…Based on the available therapeutic evidence and excellent safety profiles, the use of biological therapies has to be considered early despite the absence of an approval for this treatment in children by the national health authorities because of the strong impact on daily tasks [20 -22]. Disease awareness beyond general ophthalmologists and pediatricians as well as an early referral to specialized uveitis centers, if the disease activity is incompletely controlled, is a prerequisite to improve outcomes [22,28,29]. Nevertheless, contraindications have to be considered, including active and latent bacterial infections and immune-pathological and immuno-oncological diseases in disposed individuals [30].…”
Section: Discussionmentioning
confidence: 99%
“…Vitreous inflammatory cells by definition should be present in all cases of active intermediate uveitis [1,90]. The cellular reaction can vary from mild to severe.…”
Section: Posterior Segmentmentioning
confidence: 99%
“…Focal vitreous opacities (snowballs) are common and always indicate active inflammation ( Fig. 1) [13,62,90]. Subsequent partial or complete posterior vitreous separation is common.…”
Section: Posterior Segmentmentioning
confidence: 99%
See 1 more Smart Citation